Pediatric Interventions in a Sanfilippo Syndrome Patient Under General Anesthesia: A Case Report - Ahmad Al Malak; Hassan Issawi; Mohammad Hassoun; Mohammad Al Halabi (Case Reports in Dentistry)
Case Presentation: A 9-year-9-month-old female was presented at our private clinic accompanied with her parents and referred from a general practitioner, and the preclinical examination revealed atypical craniofacial structure and skeletal features such as abnormal posture and movements adding on atypical behavioral manifestations such as temper tantrums, speech difficulties, dementia, and destructive behavior.